2007
DOI: 10.1007/s11223-007-0072-7
|View full text |Cite
|
Sign up to set email alerts
|

Glass fracture in edge flaking

Abstract: Fracture resistance of technical quartz and normal window glasses was investigated in testing polished rectangular parallelepipeds by edge flaking their long edges with Rockwell and Vickers indenters (EF method) and by scratching the specimen surface with a Rockwell indenter followed by flaking its edge (S+EF method). It was established that the fracture of those glass specimens in their edge flaking with a Rockwell indenter was started with the formation of a Hertzian ring crack and their corresponding chip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The comparison of the present test results with those obtained earlier [4,11], has shown that, while not contradicting each other, these results only increase the amount of useful information on the behavior of glasses under the loading conditions considered. In the analysis, the results were plotted on the base diagram [12] where both the relation between the fracture resistance F R and the critical stress intensity factor K c I values (the EF base line) [5] and the relation constructed using the values of the fracture resistance F RV of specimens in edge flaking caused by indentations with a Vickers indenter [11] are presented (Fig.…”
supporting
confidence: 76%
“…The comparison of the present test results with those obtained earlier [4,11], has shown that, while not contradicting each other, these results only increase the amount of useful information on the behavior of glasses under the loading conditions considered. In the analysis, the results were plotted on the base diagram [12] where both the relation between the fracture resistance F R and the critical stress intensity factor K c I values (the EF base line) [5] and the relation constructed using the values of the fracture resistance F RV of specimens in edge flaking caused by indentations with a Vickers indenter [11] are presented (Fig.…”
supporting
confidence: 76%
“…Then the chip separates from its body when the contact point of the indenter approaches closer the specimen edge. And the chip scar on the side surface acquires the form of a Hertzian quasi-cone [21]. Secondary cracks continue growing till no less than a half of the ring crack is formed, then only fragments of ring cracks develop without additional cracking (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the early works, Almond and McCormick (1986) examined chipping of various brittle materials using a conical diamond indenter and observed that the size of chip scars depended on the indentation distance d (distance between an indentation point and an edge). Also, several researches investigated the critical indent force F required for edge chipping and found that there were linear correlation between F and d (Chai and Lawn 2007a;Gogotsi and Mudrik 2009;Gogotsi et al 2007;Morrell and Gant 2001). The ratio of F to d is referred to as "edge toughness" and the edge toughness depends only on the investigated material and the indenter geometry (Danzer and Hangl 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of F to d is referred to as "edge toughness" and the edge toughness depends only on the investigated material and the indenter geometry (Danzer and Hangl 2001). Therefore, several attempts have been made to predict the fracture toughness K c from the edge toughness whose value is given by the edge chipping test (Chai and Lawn 2007b;Danzer and Hangl 2001;Gogotsi 2013;Gogotsi and Mudrik 2009;Gogotsi et al 2007;Morrell and Gant 2001). For example, Chai and Lawn (2007b) performed the edge chipping tests of soda-lime glass by Vickers indentation and reported that they could provide the value of K c directly from the critical indent force F to within an accuracy of about 25%.…”
Section: Introductionmentioning
confidence: 99%